2017
DOI: 10.1002/2016wr019874
|View full text |Cite
|
Sign up to set email alerts
|

Forward and back diffusion through argillaceous formations

Abstract: The exchange of solutes between aquifers and lower‐permeability argillaceous formations is of considerable interest for solute and contaminant fate and transport. We present a synthesis of analytical solutions for solute diffusion between aquifers and single aquitard systems, validated in well‐controlled experiments, and applied to several data sets from laboratory and field‐scale problems with diffusion time and length scales ranging from 10−2 to 108 years and 10−2 to 102 m. One‐dimensional diffusion models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 37 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Analytical solutions were derived to analyze the diffusive flux exchange between aquifer and a single aquitard layer with the thickness varying from centimeters to hundreds of meters [85]. One-dimensional analytical solutions were derived to analyze the impacts of an exponential depleting source and back diffusion from LPPM on long tailings of BTCs [11].…”
Section: Analytical Modeling Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Analytical solutions were derived to analyze the diffusive flux exchange between aquifer and a single aquitard layer with the thickness varying from centimeters to hundreds of meters [85]. One-dimensional analytical solutions were derived to analyze the impacts of an exponential depleting source and back diffusion from LPPM on long tailings of BTCs [11].…”
Section: Analytical Modeling Studiesmentioning
confidence: 99%
“…One-dimensional analytical solutions were derived to analyze the impacts of an exponential depleting source and back diffusion from LPPM on long tailings of BTCs [11]. However, the abovementioned analytical and semi-analytical solutions could only be applied to 1D saturated porous systems [11,48,84,85]. In addition, several semianalytical/analytical models were coupled to numerical transport simulators to eliminate the limitations of analytical approaches.…”
Section: Analytical Modeling Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicated that low permeability porous media (LPPM) or aquitard region behave as a sink during contaminant loading period and as a source when the contaminant source is removed or isolated (Chapman and Parker 2005;Chapman et al, 2012;Guo and Brusseau 2017a;Yang et al 2017a;b). LPPM caused long plume tailing for a longer duration due to de-sorption (Brown et al 2012).…”
Section: Literature Survey Of Studies That Emphasized Low Permeabilit...mentioning
confidence: 99%